Identifikasi Jenis Aliran Pada Sistem Pipa Bertekanan Dengan Pompa Seri Dan Paralel - Hotman Ginting; Jimy Lingga; Jufrizal Jufrizal; Indra Hermawan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Centrifugal pumps are widely used to move fluids through increased pressure efficiently. This study examines the effect of series and parallel pump configurations and valve opening variations on flow characteristics in a pressurized piping system. A laboratory experiment method with two repetitions was used. The results showed turbulent flow at 50%, 75%, and 100% valve openings with Reynolds numbers above 10,000. In comparison, at a 25% opening, series pumps tend to produce laminar flow (Re < 600), and parallel pumps maintain transitional/turbulent flow (Re > 4,000). The recommendation is to use series pumps for high pressure and parallel for large discharge, with a minimum valve opening of 25% for optimal efficiency.